1999
DOI: 10.1038/sj.cgt.7700006
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal gene therapy with adenoviral-mediated p53 tumor suppressor gene for ovarian cancer model in nude mouse

Abstract: In an effort to develop a method for better local control of advanced ovarian cancers, we have established a peritoneal tumor model of ovarian cancer in the nude mouse and applied intraperitoneal gene therapy with the recombinant adenoviral-mediated wild-type p53 tumor suppressor gene (Avp53). The results indicate that: (a) the recombinant adenoviral vector system effectively infected the tumor and normal cells in the peritoneal cavity; and (b) Avp53 treatment effectively suppressed the growth of peritoneal tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Adenovirus was generated as described by Kim et al (1999). Briefly, pDACMV-IRF-1 was generated by the insertion of 1.8 kb EcoR1 fragment of human IRF-1 from pVL1932-IRF-1 (kind gift from Dr Takashi Fujita, The Tokyo Metropolitan Institute of Medical Science, Japan) into pDACMVp(A).…”
Section: Construction Of Adenovirus Expressing Irf-1mentioning
confidence: 99%
“…Adenovirus was generated as described by Kim et al (1999). Briefly, pDACMV-IRF-1 was generated by the insertion of 1.8 kb EcoR1 fragment of human IRF-1 from pVL1932-IRF-1 (kind gift from Dr Takashi Fujita, The Tokyo Metropolitan Institute of Medical Science, Japan) into pDACMVp(A).…”
Section: Construction Of Adenovirus Expressing Irf-1mentioning
confidence: 99%
“…cer model, 9 and the administration of BAX-expressing adenovirus was capable of eradicating Ͼ99% of ovarian tumor implants. 10 A phase I trial suggested that adenovirus-mediated gene therapy using anti-erbB2-directed intrabody is feasible in the human ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In ongoing studies, the replicationdeficient adenovirus type 5 is mostly favored over alternatively available viral vector systems for gene delivery into tumor cells. [1][2][3][4] Due to its ability to transfer genes into non-dividing cells this highly infectious adenoviral system was found to be also suitable for treatment of malignancies characterized by a low mitotic index.…”
Section: Introductionmentioning
confidence: 99%